Biomineralized gold nanoparticles along with endophytic bacterial taxa in needles of Norway spruce (Picea abies) - Lehosmaa, Kaisa; Wäli, Piippa R.; Sutinen, Aleksi; Koskimäki, Janne J.; Middleton, Maarit; Ahonen, Saija H.K.; Männistö, Minna; Pirttilä, Anna Maria; Sutinen, Raimo (BioMed Central, 2025)
Background: Biogeochemical techniques are used increasingly in mineral exploration to identify deposits under the sediment cover, or deep in the bedrock. Accordingly, localized biomineralized trace elements are reported in trees, but mechanisms and factors affecting the mineralization process in plant tissue are largely unknown. Localization of commercially important metals, such as gold (Au) and silver (Ag), and their vascular trafficking mechanism in trees are still poorly understood. Microorganisms play a key role in biomineralization due to their ability to influence the formation and deposition of minerals, directly or indirectly. We hypothesized a linkage between the presence of Au-nanoparticles and endophytic bacterial communities in Norway spruce needles. Therefore, we sampled 138 needles collected from 23 individual trees growing on Au mineralization in Northern Finland. We used field emission scanning electron microscopy (EDS-FE-SEM) to detect Au-nanoparticles and 16S rRNA amplicon sequencing to describe the endophytic bacterial community composition. Results: Altogether four spruce individuals, representing 17.4% of the sampled population, contained Au-nanoparticles. The Au-nanoparticles were surrounded by microbial cells encapsulated in a biofilm matrix. The bacterial richness was lower in trees with high Au concentrations, while bacterial diversity and community composition in spruce needles had no difference between trees with and without Au-nanoparticles. However, both machine learning algorithms and statistical indicator species analysis identified bacterial taxa linked with Au nanoparticle-rich needles. Conclusions: Our results suggest that Au-nanoparticles are associated with taxa such as P3OB-42, Cutibacterium, and Corynebacterium in Norway spruce needles. We conclude that microbes, specifically endophytic bacteria, can have a role in biomineralization processes in plants.
Keywords: amplicon sequencing; 16S rRNA; endophytic communities; AU-NANOPARTICLES; EDS-FE-SEM; Biomineralization